Evaluasi Proses Bisnis Menggunakan Metode Quality Evaluation Framework (QEF) (Studi Pada Bagian E-Government Dinas Komunikasi dan Informatika Kabupaten Gresik) - Fajar Ubaidillah Ahmad; Buce Trias Hanggara; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The Communication and Informatics Office of Gresik Regency is the office of the communication and informatics office of Gresik Regency, East Java province. The Office of Communication and Information of Gresik Regency has the task of organizing government affairs in the field of communication and informatics for the Gresik Regency area, East Java. The business process at the Gresik regency communication and information office is supported by a Standard Operating Procedure (SOP) which must be carried out by certain parties from beginning to end relating to existing work programs. There is a business process at the Gresik Regency Communication and Information Office that has not been going well. In the task